The presence of technology in Rural Education: mapping of national scientific production of the last five years - Vagner Viera de Souza; Elaine Corrêa Pereira; Celiane Costa Machado (Revista Brasileira de Educação do Campo, 2018)
The objective of this article is to map the Brazilian academic productions, within the SciELO digital library, which will address the topics of Technology and Education in the rural areas. In order to visualize the current national scenario in relation to the publications related to technology in the rural schools, we search for Portuguese-language works with the following keywords: Technology in Education, Rural Education and Rural Education Technology. With the results, we performed a comparative analysis between the total production recovered and production from the period from 2013 to 2017. Thus, we can identify in which fields of study the searches are more advanced in relation to the publications and, where we find less results, such as those refer to Technology and Rural Education, which may attract new research and publications in these less-exploited areas.